Implementasi Kaidah Yutaḥammal al-Ḍarar al-Khās Lidaf’i al-Ḍarar al-‘Ᾱm dalam Karantina Kesehatan Pasien Penyakit Menular - Rahmat Rahmat; Dewi Indriani; Sri Wahyuni (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
The rules of yutaḥammal al-ḍarar al-khās lidaf'i al-ḍarar al-'ām jurisprudence are an important basis in establishing health quarantine policies for infectious disease patients. The aim of this research is to analyze the application of these rules in health quarantine to prevent the spread of infectious diseases. This research is library research with a qualitative approach. Data collection was carried out through literature studies of relevant primary and secondary data sources. Data analysis uses deductive content analysis based on the framework of the rules of yutaḥammal al-ḍarar al-khās lidaf'i al-ḍarar al-'ām jurisprudence. The results of the study show that this rule is in line with the recommendations of the Prophet Muhammad. in several hadiths to carry out health quarantine for the public benefit. Even though quarantine can cause individual harm to patients in the form of restrictions on freedom, it is still justified according to this rule because it aims to prevent greater harm. Thus, the implementation of health quarantine is in line with the rules of the jurisprudence of yutaḥammal al-ḍarar al-khās lidaf'i al-ḍarar al-'ām. The implication is that quarantine policies remain relevant for infectious disease patients as an effort to prevent transmission that could harm the wider community.